MENGEMBANGKAN NUMERASI ANAK USIA DINI MELALUI PERMAINAN TRADISIONAL - Baiq Rofina Arvy (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This study aims to explain how to develop early childhood numeracy through traditional games. The research method used is literature study. The conclusion in this study is that the development of early childhood numeracy can be done by utilizing traditional games because many mathematical concepts are contained in traditional games. Traditional games that can be used to develop numeracy in early childhood include engklek, congklak and marbles. Through these traditional games, children can recognize patterns, numbers, geometry, measurement and data analysis.